Sintesis Nanopartikel Perak Menggunakan Bioreduktor Ekstrak Daun Pucuk Idat (Cratoxlum glaucum) dengan Metode Iradiasi Microwave - Verry Andre Fabiani; Desti Silvia; Dinda Liyana; Herul Akbar (Jurnal Kimia Fullerene, 2019)
Synthesis of silver nanoparticles was carried out using bioreductors of Cratoxylum glaucum leaf extract using the microwave irradiation method. Synthesis was carried out by reacting the Cratoxylum glaucum leaf extract with silver nitrate solution at a mass ratio of 1: 2. The variables of this study were variations in silver nitrate concentration and synthesis time. Based on the results of UV-Vis analysis showed the presence of maximum wavelength absorption which is characteristic of the formation of silver nanoparticles at a wavelength of 398.8 nm with a concentration of 0.5 mM AgNO3 and a synthesis time of 120 seconds. Particle size analysis shows that the 10% particle size distribution is 92.5 nm and overall is 544.1 nm. Antibacterial activity test results showed silver nanoparticles have strong antibacterial properties against E. coli and S. aureus bacteria.